Melanoma vaccines - Schadendorf, Dirk (Drug news & perspectives, 2000)
Several different approaches to fighting melanoma are currently being actively explored utilizing the host's immune system. These include augmentation of the immunogenicity of tumor cells by gene modification with cytokine genes and the use of T cell-defined melanoma-associated peptides, either directly for immunization (peptide vaccines) or after loading onto professional antigen-presenting cells such as dendritic cells (dendritic cell-based vaccines). Preclinical studies provided the regulatory, mechanistic and functional principles for cytokine gene-modified tumor vaccines and led to a number of phase I/II studies, including trials with IL-7-, IL-12-, GM-CSF- or interferon gamma-secreting tumor cell vaccines or IL-2 gene-transfected cell-based vaccines. Results from other clinical studies suggest that peptide immunization may represent a potentially effective means of treatment and that vaccination with autologous dendritic cells generated from peripheral blood is a safe and promising approach. The above strategies for the treatment of melanoma have shown encouraging results, although the number of patients treated in each clinical trial was small.
Gesehen am 25.11.2020